Pharmacogenetic Implications of eNOS Polymorphisms (Glu298Asp, T786C, 4b/4a) in Cardiovascular Drug Therapy - COZMA, ANGELA (In Vivo, 2019)
Endothelial nitric oxide synthase (NOS3 or eNOS) is the enzyme responsible for the highest production of nitric oxide, with the greatest impact on the cardiovascular system, encoded by the eNOS gene, which presents various polymorphisms. ENOS gene polymorphisms play an important role in the response to drugs affecting nitric oxide (NO) signaling. This review discusses the pharmacogenetic impact of eNOS polymorphisms on the response to drugs affecting NO activity: angiotensin converting enzyme inhibitors, angiotensin II receptor antagonists, calcium blockers, beta-blockers, diuretics, phosphodiesterase inhibitors, and statins. The identification of biomarkers that accurately predict particular phenotypes is a challenge that needs additional large studies, in different populations. Efforts should be oriented towards a more accurate evaluation of the effects of eNOS genetic variants on biochemical parameters reflecting eNOS gene expression and enzymatic activity, in different diseases, as well as following drug treatment. This approach will allow for a better understanding of the role of eNOS genetic variants in cardiovascular disease progression and for cardiovascular drug therapy optimization.